The Open Burning of Plastic Wastes is an Urgent Global Health Issue - Gauri Pathak; Mark Nichter; Anita Hardon; Eileen Moyer (Annals of Global Health, 2024)
The open burning of mixed wastes that contain plastics is a widespread practice across the globe, resulting in the release of gas emissions and ash residues that have toxic effects on human and environmental health. Although plastic pollution is under scrutiny as a pressing environmental concern, it is often conflated with plastic litter, and the contribution of the open burning of plastics to air, soil, and water pollution gets overlooked. Therefore, campaigns to raise awareness about plastic pollution often end up leading to increased open burning. Many countries or regions where open burning is prevalent have laws in place against the practice, but these are seldom effective. In this viewpoint, we direct attention to this critical but largely overlooked dimension of plastic pollution as an urgent global health issue. We also advocate interventions to raise awareness about the risks of open burning and emphasize the necessity of phasing out some particularly pernicious plastics in high-churn, single-use consumer applications.